Giant Cell Tumor of the Tendon Sheath of the Hand: Analysis of Factors Impacting Recurrence - Pavan Venkateswar Kolisetty; Sheikh Sarfraz Ali; Imran Ahmad; Indrajith K. Sudhy; Om Prakash; Y. Ranga Kishore (Indian Journal of Plastic Surgery)
Background Giant cell tumors of the tendon sheath (GCTTS) of the hand are considered the second most common benign tumors of the hand after ganglion cysts. Excision biopsy is considered the standard treatment at present. They are notorious for having a very high rate of recurrence as given in many studies. Many factors are said to be associated with recurrence of the tumors. The goal of this study is to evaluate the long-term results of a series of 48 patients operated on at a single institute and to find out if there is any correlation between the proposed risk factors with recurrence.